2015
DOI: 10.1093/mnras/stv836
|View full text |Cite
|
Sign up to set email alerts
|

The turbulent origin of spin–orbit misalignment in planetary systems

Abstract: The turbulent environment from which stars form may lead to misalignment between the stellar spin and the remnant protoplanetary disk. By using hydrodynamic and magnetohydrodynamic simulations, we demonstrate that a wide range of stellar obliquities may be produced as a by-product of forming a star within a turbulent environment. We present a simple semi-analytic model that reveals this connection between the turbulent motions and the orientation of a star and its disk. Our results are consistent with the obse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(114 citation statements)
references
References 68 publications
6
107
1
Order By: Relevance
“…However, our earlier direct imaging survey finds no correlation between the orbital properties of the transiting planet and stellar multiplicity, suggesting that KozaiLidov migration is probably not the dominant channel for the generation of hot Jupiter spin-orbit misalignment. Instead, our results signal broad agreement with the primordial excitation of stellar obliquities (e.g., Lai 2014; Spalding & Batygin 2014Fielding et al 2015).…”
Section: Introductionsupporting
confidence: 71%
“…However, our earlier direct imaging survey finds no correlation between the orbital properties of the transiting planet and stellar multiplicity, suggesting that KozaiLidov migration is probably not the dominant channel for the generation of hot Jupiter spin-orbit misalignment. Instead, our results signal broad agreement with the primordial excitation of stellar obliquities (e.g., Lai 2014; Spalding & Batygin 2014Fielding et al 2015).…”
Section: Introductionsupporting
confidence: 71%
“…Fielding et al (2015) found from their simulations of turbulent fragmentation typical spin-orbit angles Φ ∼ 40…”
Section: Discussionmentioning
confidence: 99%
“…Our evolution model takes into account the accretion history, which determines the protostellar size and nuclear state as well as the protostellar mass. The direction of angular momentum of the accreting material determines the outflow launching direction, as described in Fielding et al (2015). By construction, magnetic flux does not accrete onto sink particles.…”
Section: Methodsmentioning
confidence: 99%
“…We are not able to follow model M4P2.5l6 for the same evolutionary time due to the prohibitive computational expense. See Fielding et al (2015) for a more thorough resolution study of protostellar properties at different resolutions.…”
Section: A Resolution Studymentioning
confidence: 99%